2015
DOI: 10.1177/1759091415592389
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Negative Charge in the Delivery of Quantum Dots to Neurons

Abstract: Despite our extensive knowledge of the structure of negatively charged cell surface proteoglycans and sialoglycoconjugates in the brain, we have little understanding of how their negative charge contributes to brain function. We have previously shown that intensely photoluminescent 9-nm diameter quantum dots (QDs) with a CdSe core, a ZnS shell, and a negatively charged compact molecular ligand coating (CL4) selectively target neurons rather than glia. We now provide an explanation for this selective neuronal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 43 publications
1
70
0
Order By: Relevance
“…Additionally, we found that the lysosomes might be long-term accumulation sites of CdTe QDs in neurons, similar to a previous study, 4 which could be partially explained by the findings of Walters et al that negative charge on the QD coating resulted in preferential uptake in neurons. 25 The pathological lesion findings could explain the impaired capabilities of learning and memory in MPAmodified CdTe QD-treated rats. However, the definite mechanisms causing this damage is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the lysosomes might be long-term accumulation sites of CdTe QDs in neurons, similar to a previous study, 4 which could be partially explained by the findings of Walters et al that negative charge on the QD coating resulted in preferential uptake in neurons. 25 The pathological lesion findings could explain the impaired capabilities of learning and memory in MPAmodified CdTe QD-treated rats. However, the definite mechanisms causing this damage is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…; Walters et al . , ), and it also might protect siRNA from digestion of intracellular RNase. Furthermore, QD‐siRNA constructs demonstrated robust knockdown of 72.0 ∓ 12.0% luciferase, which is similar or better than commercial transfection reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if the compact ligand or PEG was positively charged or the extracellular matrix was enzymatically digested with chondroitinases (Walters et al . ), the QDs were targeted more to oligodendrocytes. This makes QDs ideal multipurpose delivery vehicles because they not only facilitate specific cell‐type delivery (Walters ) and are non‐toxic, but also allow for real‐time tracking of their location in vitro , eliminating the need for the addition of fluorescent tags to track progress.…”
mentioning
confidence: 97%
See 2 more Smart Citations